1984
DOI: 10.1557/proc-38-35
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, Velocity, and Species Mapping in an Induction Plasma

Abstract: As part of an effort to determine the feasibility of carbothermic reduction of alumina in plasmas, spatial distributions of temperature, velocity and species in the plume of an argon radio-frequency plasma with alumina and carbon additions were estimated using a two dimensional theoretical model of the flow field and a thermochemical model based on equilibrium conditions. Experimentally determined boundary conditions were input to the models. Using a 30 kW inductively coupled plasma, experimental measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…[ 77,78 ] Moreover, the feed‐restricted birds might have mobilized the body fats to meet the prevailing energy demand during restriction. [ 81,82 ] The current findings concur with those of Omosebi et al. [ 41 ] and Boostani et al.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…[ 77,78 ] Moreover, the feed‐restricted birds might have mobilized the body fats to meet the prevailing energy demand during restriction. [ 81,82 ] The current findings concur with those of Omosebi et al. [ 41 ] and Boostani et al.…”
Section: Resultssupporting
confidence: 93%
“…[77,78] Moreover, the feed-restricted birds might have mobilized the body fats to meet the prevailing energy de-mand during restriction. [81,82] The current findings concur with those of Omosebi et al [41] and Boostani et al [40] who reported a lower abdominal in FR birds. Contrarily, Demir et al [3] did not observe changes in abdominal fat following FR in birds while FR for 6 h d −1 from third to fourth week and from fourth to fifth week improved abdominal fat in broilers.…”
Section: Carcass Traits and Fat Depotssupporting
confidence: 92%
See 1 more Smart Citation